Konstribusi Tafsir Kontemporer dalam Menjawab Persoalan Ummat - Muhammad Amin (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2013)
Interpretation is a means to explain the holy message of the Koran to be widely understood by many and practiced in real life. Interpretation of the Qur’an has been going on for a long time, starting from the time he was demoted to the present and even the future. The Qur’an is also a scripture that applies to all Muslims wherever and whenever it is. Efforts to interpret the Qur’an in the present or the better known contemporary interpretation has a very strategic role in the realm of Islamic scholarship. The development of information technology has brought such tremendous influence on the lifestyle of modern society. It also contributes to the development raises new issues in the various dimensions of life. The issue is so complex and the solution certainly needed a way out so that the Muslim community in particular human life running harmoniously. Interpretation of the Qur’an is done by experts in the contemporary era has been a lot of investigating and talking about a variety of issues. This short article will discuss about the contribution of the interpretation of contemporary in an effort to provide solutions to the various problems of the ummah